2017
DOI: 10.1509/jppm.13.125
|View full text |Cite
|
Sign up to set email alerts
|

The Stigma of Mental Illness: Using Segmentation for Social Change

Abstract: Despite the unequivocal incidence and burden that mental illnesses place on the world, those with mental illness remain not only neglected but also deeply stigmatized across societies. The stigma that surrounds mental illness serves as a barrier to treatment and recovery, leading to serious negative consequences such as school failure, job loss, and suicide. While many large-scale social marketing efforts have found some success in reducing stigma, we contend that the recommended approaches, which utilize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…Primary caregivers whose relatives were previously admitted to hospital, were discharged to be cared for at home and were admitted to hospital again at the time of data collection were included. Serious mental illness was limited to bipolar, schizophrenia and major depression as these chronic disorders were identified to be common in developing countries [ 21 , 22 ] including South Africa [ 23 ]. These inclusion criteria, therefore, supported the objective of the current study.…”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary caregivers whose relatives were previously admitted to hospital, were discharged to be cared for at home and were admitted to hospital again at the time of data collection were included. Serious mental illness was limited to bipolar, schizophrenia and major depression as these chronic disorders were identified to be common in developing countries [ 21 , 22 ] including South Africa [ 23 ]. These inclusion criteria, therefore, supported the objective of the current study.…”
Section: Study Methodsmentioning
confidence: 99%
“…Children of parents with mental illness are at risk of psychiatric and behavioural problems which include poor academic performance, inability to sustain committed relationships, alcohol and drug problems as well as problems with the law [ 14 ]. Moreover, families of patients with mental disorders also deal with financial strains, the disruption of domestic routine, constraints to social and leisure time, physical violence, damage to property presenting challenges to the families as well as the stigma that is commonly directed at people with mental illness [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…That services marketing suggestion of simply sitting with a consumer patient to understand more clearly his/her journey and experiences brings about another line of research directions-a different kind of focus on the consumer patient. In general, I was quite surprised that the literature indicated that marketers rarely consider issues related to mental health (though see Yeh et al, 2017, and of course the rising literature in marketing on well-being is presumably the flip side). My surprise arose in part due to the prevalence of psychological training throughout the consumer behavior marketing academic community;…”
Section: Consumer Behavior the Micro-patient-levelmentioning
confidence: 99%
“…Another notable gap is the limited use of the segmentation process outlined in Dietrich et al (2017a). While some evidence of targeting based on a single variable was evident (Boonrod et al, 2015), the adoption of data-driven segmentation profiling, such as two-step cluster analysis (Arli et al, 2017;Dietrich, 2017;Gomez et al, 2018;Gray and Bean, 2011;Kim et al, 2019;Poortinga and Darnton, 2016;Tkaczynski et al, 2016;Yeh et al, 2017) to identify homogeneous groups in a heterogeneous population was not reported in interventions identified in this review. Interventions in our review predominantly targeted groups based on a selected characteristic, such as housing type or location, which overlooks differences that exist in the population.…”
Section: Studymentioning
confidence: 91%